Sustainability Relationship Between Space Configuration, Activity Patterns, and Mosque Acoustics Quality - Nur Rahmawati Syamsiyah; Atyanto Dharoko; Sentagi Sesotya Utami; Afizah Ayob (Department of Architecture, Faculty of Science and Technology, UIN Maliki Malang, 2022)
The Great Mosque of Yogyakarta was built in 1773. This mosque has a traditional architectural style. This study investigates the relationship between the mosque's architectural form, the activities inside it, and its acoustic characteristics. It employed quantitative and qualitative methods, including sound pressure level (SPL) measurement, reverberation time, and architectural and activity observations. Acoustic measurements, architectural observations, and activities are conducted inside and outside the mosque from morning to night for one week. The research finding is a spatial continuity pattern identified as the gradation of SPL value. Consistent continuity of SPL values in accordance with the nature of activities hierarchy. The result of this study is to improve mosque noise control by arranging outdoor and indoor spaces in a sustainable manner.